Dissociating Bottom-Up and Top-Down Mechanisms in the Cortico-Limbic System during Emotion Processing. (27th August 2014) - Comte, Magali; Schön, Daniele; Coull, Jennifer T.; Reynaud, Emmanuelle; Khalfa, Stéphanie; Belzeaux, Raoul; Ibrahim, El Chérif; Guedj, Eric; Blin, Olivier; Weinberger, Daniel R.; Fakra, Eric
Abstract: The cortico-limbic system is critically involved in emotional responses and resulting adaptive behaviors. Within this circuit, complementary regions are believed to be involved in either the appraisal or the regulation of affective state. However, the respective contribution of these bottom-up and top-down mechanisms during emotion processing remains to be clarified. We used a new functional magnetic resonance imaging (fMRI) paradigm varying 3 parameters: emotional valence, emotional congruency, and allocation of attention, to distinguish the functional variation in activity and connectivity between amygdala, anterior cingulate cortex (ACC), and dorsolateral prefrontal cortex (DLPFC). Bottom-up appraisal of negative compared with positive stimuli led to a greater amygdala response and stronger functional interaction between amygdala and both dorsal ACC and DLPFC. Top-down resolution of emotional conflict was associated with increased activity within ACC and higher functional connectivity between this structure, and both the amygdala and DLPFC. Finally, increased top-down attentional control caused greater engagement of the DLPFC, accompanied by increased connectivity between DLPFC and dorsal ACC. This novel task provides an efficient tool for exploring bottom-up and top-down processes underlying emotion and may be particularly helpful for investigating the neurofunctional underpinnings of psychiatric disorders.